ANALYSIS OF THE READINESS OF THE IMPLEMENTATION OF THE ONLINE TICEKTING SYSTEM PERCEIVED BY SERVICE USERS AND PORT OFFICERS AT THE MARISA FERRY PORT GORONTALO PROVINCE - Sutrisno, Slamet Prasetyo; Triwahyuni, Siti Nurlaili; Surnata, Surnata; Arkani, Hari; Zahara, Zahara (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2024)
Marisa Ferry Port is a port that connects Gorontalo and Central Central Sulawesi. Ticket purchasing process ticket purchase process at Marisa Ferry Port still uses the manual method by queuing and having to wait for a long time at the port counter. at the port counter, because it has not using an online ticketing system. To improve the quality of service in booking tickets to users services, so this research aims to determine the readiness of service users and port officials port officers towards the implementation of an online ticketing system system in the ticket purchasing process at the Marisa Ferry Port, Gorontalo Province. Gorontalo Province. This research uses a quantitative approach with observation, documentation and questionnaire. Data collection was conducted by distributing questionnaires to service users and Marisa Ferry Port officers as respondents to obtain data on the level of readiness of service users and port officers. data on the level of readiness of service users and port officials. Based on the results of the analysis, it is known that the percentage of service user readiness is 93% and the readiness of port officials is 78%, indicating that service users and port officials are already ready. indicates that service users and port officials have fully support the implementation of Ministerial Regulation Ministerial Regulation No. 19 of 2020 to implement an online ticketing system at the Marisa Crossing Port. Marisa Crossing Port. For this reason, port organizers are expected to immediately realize online ticket purchases, prepare supporting facilities for online tickets and socialize to the public regarding changes in the ticket purchase system from manual to online using ferrizy applications and websites.